The Earnings and Labor Supply of U.S. Physicians - Joshua D Gottlieb; Maria Polyakova; Kevin Rinz; Hugh Shiplett; Victoria Udalova (The Quarterly Journal of Economics, 2025)
Abstract Is government guiding the invisible hand at the top of the labor market? We use new administrative data to measure physicians’ earnings and estimate the influence of health care policies on these earnings, physicians’ labor supply, and the allocation of talent. Combining the administrative registry of U.S. physicians with tax data, Medicare billing records, and survey responses, we find that physicians’ annual earnings average $350,000 and make up 8.6% of national health care spending. Business income makes up one-quarter of earnings and is systematically underreported in survey data. Earnings increase steeply early in the career, and there are major differences across specialties, regions, and firm sizes. The geographic pattern of earnings is unusual compared with other workers. We argue that these patterns reflect policy choices to subsidize demand for physician care, amplified by restrictions on physician entry, especially in certain specialties. Health policy has a major impact on the margin: 25% of physician fee revenue driven by Medicare reimbursements accrues to physicians personally. Physicians earn 8% of public money spent on insurance expansion. These policies in turn affect the type and quantity of medical care physicians supply, retirement timing, and the allocation of talent across specialties.